2020
DOI: 10.1101/2020.09.09.285445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Safety and Immunogenicity of an Adjuvanted, TH-1 Skewed, Whole Virion InactivatedSARS-CoV-2 Vaccine - BBV152

Abstract: We report the development and evaluation of safety and immunogenicity of a whole virion inactivated SARS-COV-2 vaccine (BBV152), adjuvanted with aluminium hydroxide gel (Algel), or a novel TLR7/8 agonist adsorbed Algel. We used a well-characterized SARS-CoV-2 strain and an established vero cell platform to produce large-scale GMP grade highly purified inactivated antigen, BBV152. Product development and manufacturing were carried out in a BSL-3 facility. Immunogenicity was determined at two antigen concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…Preclinical studies on BBV152 adjuvanted with this molecule reported a Th1-biased response in mice. 7 Furthermore, in a non-human primate and hamster live viral challenge studies, Algel-IMDG formulations led to higher neutralising antibodies, which might have resulted in improved upper and lower airway viral clearance (after challenge). 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies on BBV152 adjuvanted with this molecule reported a Th1-biased response in mice. 7 Furthermore, in a non-human primate and hamster live viral challenge studies, Algel-IMDG formulations led to higher neutralising antibodies, which might have resulted in improved upper and lower airway viral clearance (after challenge). 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies in mice, rats, and rabbits showed appropriate safety profiles and humoral and cell-mediated responses. 7 Two live viral challenge protective efficacy studies in hamsters and non-human primates were done. In both studies, protection was evident by rapid clearance of virus in the lower and upper respiratory tract, and absence of lung pathology (after viral challenge).…”
Section: Introductionmentioning
confidence: 99%
“…G clade sequences are predominantly circulating in India and contribute to~74% of the SARS-CoV-2 sequences circulating in the world [26][27][28] . The genetic stability of the NIV-2020-770 strain was demonstrated by multiple passages in Vero CCL-81 cells and by next-generation sequencing 7 . Virus propagation was done in a bioreactor (Corning Life Science) at the temperature of 36 ± 1°C and was harvested at 36-72 h post infection and supernatants were collected, clarified and aliquoted.…”
Section: Methodsmentioning
confidence: 99%
“…The safety and the immunogenicity of inactivated vaccine candidate BBV152 has been established in mice, rat and rabbit models 7 .The vaccine candidate has been found to induce an effective humoral immune response and protects Syrian hamsters from SARS-CoV-2 pneumonia 8 . Here, we report the assessment of immunogenicity and protective efficacy of three formulations of a purified whole-virion-inactivated SARS-CoV-2 vaccine candidate BBV152 in the rhesus macaques.…”
mentioning
confidence: 99%
“…Covaxin (BBV152) (3 or 6 µg) injected with aluminum hydroxide gel or a TLR7/8 agonist absorbed gel as adjuvant demonstrated good immunogenicity in mice, rats, and rabbits [ 137 ]. The injection of Covaxin (3 µg) and TLR7/8 agonist absorbed gel in a 2-doses vaccination scheduled 14 days apart provides an immune protection to macaques when challenged by SARS-CoV-2 [ 138 ].…”
Section: Inactivated Vaccinesmentioning
confidence: 99%